2011
DOI: 10.1109/tsp.2011.2157913
|View full text |Cite
|
Sign up to set email alerts
|

Performance Bounds for Expander-Based Compressed Sensing in Poisson Noise

Abstract: Abstract-This paper provides performance bounds for compressed sensing in the presence of Poisson noise using expander graphs. The Poisson noise model is appropriate for a variety of applications, including low-light imaging and digital streaming, where the signal-independent and/or bounded noise models used in the compressed sensing literature are no longer applicable. In this paper, we develop a novel sensing paradigm based on expander graphs and propose a MAP algorithm for recovering sparse or compressible … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…Some of the major theoretical challenges associated with the application of CS to linear optical systems in the presence of Poisson noise have been addressed in the recent literature [38,39]. These works considered two novel sensing paradigms, based on either pseudo-random dense sensing matrices (akin to the shifted and scaled dense sensing matrix described above) or expander graph constructions, both of which satisfy the nonnegativity and flux preservation constraints.…”
Section: Sidebar] Sparse Recovery: Methods and Guaranteesmentioning
confidence: 99%
“…Some of the major theoretical challenges associated with the application of CS to linear optical systems in the presence of Poisson noise have been addressed in the recent literature [38,39]. These works considered two novel sensing paradigms, based on either pseudo-random dense sensing matrices (akin to the shifted and scaled dense sensing matrix described above) or expander graph constructions, both of which satisfy the nonnegativity and flux preservation constraints.…”
Section: Sidebar] Sparse Recovery: Methods and Guaranteesmentioning
confidence: 99%
“…The case of a Poisson single-measurement model (without perturbation on the sensing matrix) has been considered in [22,24]. However, it is worth noting that even though the multiple-measurement case can be formulated concisely as y ∼ Pois(Af + λ), akin to the single-measurement situation [22,24], a fundamental difference is that the sensing matrix A in this case is limited to a block-diagonal structure, rather than being arbitrary, as in the single-measurement case. The block-diagonal measurement matrix poses a more challenging (and practical) problem.…”
Section: Concentration-of-measure Inequalitiesmentioning
confidence: 99%
“…The block-diagonal measurement matrix poses a more challenging (and practical) problem. Hence, the proof techniques from [22,24] cannot be applied to the multiple-measurements case, and the nonnegativity constraint on the sensing matrix also invalidates adaptation of the results in [8,21].…”
Section: Concentration-of-measure Inequalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we evaluated CS approaches for generating high resolution images and video from photon-limited data. 59,60 In particular, we showed how a feasible positivity-and flux-preserving sensing matrix can be constructed, and analyzed the performance of a CS reconstruction approach for Poisson data that minimizes an objective function consisting of a negative Poisson log likelihood term and a penalty term which measures image sparsity. We showed that for a fixed image intensity, the error bound actually grows with the number of measurements or sensors.…”
Section: Non-negativity and Photon Noisementioning
confidence: 99%